A facile method for the fast and accurate selection of a UF membrane for membrane bioreactors. Issue 11 (28th September 2021) - Li, Zhengtao; Tio, Wee; Sun, Darren D.
Abstract : A facile method for the fast and accurate selection of a UF membrane for MBR wastewater reclamation. Abstract : Membrane fouling is the bottleneck restricting membrane bioreactors (MBRs) from being widely used for water reclamation. How to select the best membrane with anti-fouling properties for MBRs is always a complicated challenge due to the lack of evaluation methods. This paper introduced a facile method using traditional cake filtration and pore blocking theory for easy and fast selection of commercially available ultrafiltration (UF) membranes for MBRs. Three commercial UF membranes were selected for evaluating the filtration performance in MBRs using this method. The testing result reveals that the NS membrane has the best anti-fouling performance with less pore blocking, and its cake fouling was easier to remove, which was consistent with the long-term MBR operation result. FE-SEM, AFM and EDX were adopted to characterize the surface topography of the three UF membranes, which explained that the anti-fouling performance of the NS membrane was likely due to its less rough surface and Ti content.